Pengaruh Edukasi melalui Metode Demonstrasi Terhadap Keterampilan Sadari Remaja Putri dalam Deteksi Dini Kanker Payudara - Siti Maisaroh; Kristina Yuniarti; Ruslinawati Ruslinawati; Yenny Okvitasari (Universitas Malahayati Lampung, 2026)
ABSTRACT Breast cancer often develops without being noticed by women. This cancer has become a serious global health concern, affecting both developed and developing countries, with increasing incidence and impact, particularly in countries with limited resources. In Indonesia, new cases of breast cancer reached 68,858 cases (16.6%) out of a total of 396,914 cancer cases, with approximately 65,000 new cases added each year. Data from the South Kalimantan Provincial Health Office reported 121 cases of breast cancer in 2023, increasing to 140 cases in 2024, and 35 cases recorded from January to September 2025.This study aimed to determine the effect of education using the demonstration method on breast self-examination (BSE/SADARI) skills among adolescent girls in early detection of breast cancer between the intervention and control groups. This study employed a quasi-experimental design with a two-group post-test only control group design. The research was conducted at SMA Negeri 1 Banjarmasin. The population consisted of 380 female students, with a sample of 80 respondents selected using proportional stratified random sampling. Data were collected using a SADARI observation checklist as the research instrument. The results of the Mann–Whitney test showed a significant difference in SADARI skills between the intervention and control groups, with a p-value of 0.000 (p 0.05). The mean rank of the intervention group (53.95) was higher than that of the control group (27.05), indicating that the demonstration-based education was more effective. These findings indicate that education using the demonstration method has a significant effect on improving SADARI skills among adolescent girls in the early detection of breast cancer. The conclusion of this study is that education through the demonstration method significantly influences the improvement of SADARI skills among adolescent girls in the early detection of breast cancer. Keywords : Demonstration, Breast cancer, SADARI. ABSTRAK Kanker payudara sering kali muncul tanpa disadari oleh para wanita. Masalah kanker ini menjadi perhatian serius di seluruh dunia, baik di negara maju maupun negara berkembang, dengan tingkat kejadian dan dampak yang semakin meningkat terutama di negara-negara dengan sumber daya terbatas. Di Indonesia, kasus baru kanker payudara mencapai 68.858 kasus (16,6%) dari total 396.914 dan bertambah sekitar 65.000 kasus baru setiap tahunnya. Data Dinas Kesehatan Provinsi Kalimantan Selatan mencatat kasus kanker payudara pada tahun 2023 sebanyak 121 kasus, meningkat pada tahun 2024 menjadi 140 kasus, dan tercatat 35 kasus pada periode Januari hingga September 2025. Tujuan penelitian ini adalah untuk mengetahui pengaruh edukasi melalui metode demonstrasi terhadap keterampilan SADARI remaja putri dalam deteksi dini kanker payudara pada kelompok intervensi dan kelompok kontrol. Penelitian menggunakan Quasi Experiment Two Group Post-Test Only Control Group Design. Penelitian dilakukan di SMA Negeri 1 Banjarmasin. Populasi dalam penelitian ini adalah siswi SMA Negeri 1 Banjarmasin sebanyak 380 siswi, Sampel sebanyak 80 responden, pemilihan sampel menggunakan Proportional Stratified Random Sampling. Pengumpulan data menggunakan instrumen penelitian yaitu lembar observasi SADARI. Hasil analisa dengan Mann Whitney menunjukkan bahwa terdapat perbedaan keterampilan SADARI antara kelompok intervensi dan kelompok kontrol dengan nilai p = 0,000 (p 0,05) dengan didapatkan dengan kelompok intervensi (53,95) efektif daripada kelompok kontrol (27,05). Hal ini menunjukkan bahwa edukasi melalui metode demonstrasi berpengaruh terhadap peningkatan keterampilan SADARI remaja putri dalan deteksi dini kanker payudara. Kesimpulan pada penelitian ini adalah terdapat pengaruh edukasi melalui metode demonstrasi terhadap keterampilan SADARI remaja putri dalam deteksi dini kanker payudara. Kata Kunci: Demonstrasi, Kanker payudara, SADARI.